Dynamics of non‐structural carbohydrates in terrestrial plants: a global synthesis. Issue 4 (November 2016) - Martínez‐Vilalta, Jordi; Sala, Anna; Asensio, Dolores; Galiano, Lucía; Hoch, Günter; Palacio, Sara; Piper, Frida I.; Lloret, Francisco
Abstract: Plants store large amounts of non‐structural carbohydrates (NSC). While multiple functions of NSC have long been recognized, the interpretation of NSC seasonal dynamics is often based on the idea that stored NSC is a reservoir of carbon that fluctuates depending on the balance between supply via photosynthesis and demand for growth and respiration (the source–sink dynamics concept). Consequently, relatively high NSC concentrations in some plants have been interpreted to reflect excess supply relative to demand. An alternative view, however, is that NSC accumulation reflects the relatively high NSC levels required for plant survival; an important issue that remains highly controversial. Here, we assembled a new global database to examine broad patterns of seasonal NSC variation across organs (leaves, stems, and belowground), plant functional types (coniferous, drought‐deciduous angiosperms, winter deciduous angiosperms, evergreen angiosperms, and herbaceous) and biomes (boreal, temperate, Mediterranean, and tropical). We compiled data from 121 studies, including seasonal measurements for 177 species under natural conditions. Our results showed that, on average, NSC account for ~10% of dry plant biomass and are highest in leaves and lowest in stems, whereas belowground organs show intermediate concentrations. Total NSC, starch, and soluble sugars (SS) varied seasonally, with a strong depletion of starch during the growing season and a general increase during winter months, particularly in boreal and temperate biomes. Across functional types, NSC concentrations were highest and most variable in herbaceous species and in conifer needles. Conifers showed the lowest stem and belowground NSC concentrations. Minimum NSC values were relatively high (46% of seasonal maximums on average for total NSC) and, in contrast to average values, were similar among biomes and functional types. Overall, although starch depletion was relatively common, seasonal depletion of total NSC or SS was rare. These results are consistent with a dual view of NSC function: whereas starch acts mostly as a reservoir for future use, soluble sugars perform immediate functions (e.g., osmoregulation) and are kept above some critical threshold. If confirmed, this dual function of NSC will have important implications for the way we understand and model plant carbon allocation and survival under stress.